2018
DOI: 10.1016/j.jgeb.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the genetic and haplotype diversity among four populations of Catla catla from Madhya Pradesh revealed through mtDNA cyto b gene sequences

Abstract: In the present investigation, the genetic structure of four populations of Catla catla, sequences of mitochondrial gene, cytochrome b (cyto b) from four populations were sequenced and analyzed. The sequences of mitochondrial regions revealed high haplotype diversity and low nucleotide diversity. The lowest 249 polymorphic sites and 0.00 parsimony informative sites were detected in populations of Fish Federation Pond (CCFFB) whereas highest 330 polymorphic sites and 56 parsimony informative sites were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…This possibility is supported by Roesma et al [35] which states that if genetic mixing between species with separate locations can still occur, then genetic similarities between species are always maintained. In line with the statements of Garg and Mishra [54] which states that gene flow has the potential to reduce genetic differentiation. Zero genetic variation between Palo fish populations based on the cytochrome b gene is also predicted because these two populations come-from the same ancestor.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This possibility is supported by Roesma et al [35] which states that if genetic mixing between species with separate locations can still occur, then genetic similarities between species are always maintained. In line with the statements of Garg and Mishra [54] which states that gene flow has the potential to reduce genetic differentiation. Zero genetic variation between Palo fish populations based on the cytochrome b gene is also predicted because these two populations come-from the same ancestor.…”
Section: Discussionsupporting
confidence: 68%
“…The number of bases in Palo fish (A+T) is higher than (G+C). According to the previous researchers [51,52,53,54,55] the number of bases (A+T) in vertebrates is higher than (G+C).…”
Section: Blast Analysismentioning
confidence: 98%
“…The genetic variation of a species is distributed both within populations, expressed as differences between individuals and between populations, expressed as differences in the presence and frequency of alleles (Garg and Mishra, 2018). In this study, analyses of the gyrA, parC and parE sequences were found to be polymorphic with high haplotype diversity (Hd) (0.945-0.982) and low nucleotide diversity (0.01225-0.02001).…”
Section: Discussionmentioning
confidence: 70%
“…Haplotypes reveal the genetic variation within a species based on the nucleotide sequence (Garg and Mishra 2018;Phillips et al 2019). There were four haplotypes (Hap) from both cattle (Table 2), namely haplotype_1 (Hap_1) found in Taro samples 1, 2, 3, 4, 5, 7, and 9, while in Bali cattle from Sobangan, it was found in numbers 1, 2, 3, 4, and 5.…”
Section: Discussionmentioning
confidence: 99%